Pengaruh Budaya Organisasi, Rotasi Kerja, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Departemen Produksi Npk Phonska Di Pabrik II PT Petrokimia Gresik - Wijanarko, Rendhy Nur Rokhim; Sukaris, Sukaris (Jurnal Mahasiswa Manajemen, 2025)
Background – Production results in the last 3 years at PT Petrokimia Gresik's phonska factory fluctuated and tended to decline. Objective – This study aims to analyze the influence of variables of organizational culture, work rotation, work discipline and work motivation on employee performance in Phonska factory. Design / Methodology / Approach – Researchers used a quantitative approach with a population of 75 production employees. The sampling technique is saturated and uses probability sampling method with the number of samples are 75 respondents. Findings – The results of the study proved that the variables of organizational culture, work discipline and work motivation had a positive and significant effect on employee performance and job rotation variables had no effect on employee performance. Research Implication – Directly the impact on the company if the factors that affect performance are not considered, the employee's performance has decreased, therefore it is necessary to do a diclap, seminar, etc. so that employees understand better and do well and obtain good performance as well. Limitations – The next researcher should be able to expand the research so that more complete information is obtained about the factors that affect employee performance, namely leadership style, work stress, education level, work experience, job satisfaction, and job loyalty. on performance.